Students' mathematical communication and collaboration patterns through small group work: A gender case study - Juraidatul Ulfa; Siti Inganah; Octavina Rizky Utami Putri (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
Social factors, including the persistence of traditional gender roles in the educational environment, often influence the low active participation of students in mathematics group discussions. Differences in communication and collaboration styles between male and female students usually result in unequal contributions in group-based learning. This study aims to examine the communication patterns and mathematical collaboration of students, based on gender, in the context of small-group work in mathematics learning. A descriptive qualitative approach with a case study design was used on 17 grade XI students at MA Muhammadiyah Bima City, who were selected purposively. Data collection techniques include observation, interviews, and documentation, which were then analyzed thematically. The results showed that female students were more active in asking questions, giving suggestions, and building structured cooperation. In contrast, male students were more dominant in explaining concepts and making decisions with a pattern of collaboration that tended to be spontaneous. These findings suggest that social norms, gender, and local culture influence the dynamics of communication and cooperation in the study group. This research underscores the pivotal role of teachers in fostering inclusive and gender-equitable learning environments, as well as in developing collaborative learning strategies that are responsive to diverse roles in group interactions.